(3JgPjH GddZIs - (3CHh efUhQ eMeO Hf CMeO Hf GdGRgQj, Hf WdMI,J (B370 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg HGH GdZjf hGdfhf Zf fZ bGd GddjK GdZfI UhJ ajg s
(3BNQgG (B:s
(3hbGd GdCUeYi gi Ohbjg THg GdNfaSGA WhjdI GdQLd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B311s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(201) s
Keywords: (3GddZIs